Safety Evaluation of Two Nigerian Polyherbal Formulations (Fidson Bitter® and Daily Living Bitter®) in Male Wistar Rats (2018)
Background: Herbal bitters are used for diverse diseases based on the manufacturers’ assertions. However, little is known about their toxicity profile. Objective: The safety profile of two commonly used herbal bitters in Nigeria (Fidson bitter® and Daily living bitter®)was evaluated in rats. Materials and Methods: Single oral dose, 2 g/kg, of each reconstituted bitter extract was administered to male and female rats in acute toxicity test. Animals were observed for 14 days for behavioral changes and mortality. In sub-acute oral toxicity experiment, 250 mg/kg and 500 mg/kg of each bitter was separately administered daily to different groups of male Wistar rats for 30 days. Safety profile of concurrent administration of these bitters was also assessed. Histopathological, hematological, and clinical chemistry indices were evaluated. Results: The LD50 was found to be >2 g/kg. Daily living bitter® (DLB) had no significant effect on any of the indices evaluated (P>0.05). However, Fidson bitter® caused significant reductions in white blood cells count (WBC) compared with the control. Concomitant administration of the bitters resulted in significant (P<0.05) weight gain (up to 33 %), reduction in WBC and congestion of the liver without corresponding increase in liver biomarkers. Conclusion: Daily living bitter® was safe in sub-acute administration while Fidson bitter®and combination of the two bitters reduced white blood cell count. Hence, caution should be exercised in using Fidson bitter® or combination of the two bitters in humans as findings suggest possibility of immune suppression.